2014
DOI: 10.1007/s00296-014-2974-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of rheumatoid arthritis in Italy

Abstract: Aim of the study was to estimate the prevalence and incidence of rheumatoid arthritis (RA) from an administrative cohort consisting of 2,268,514 males and 2,446,769 females, aged ≥ 18 years, from 32 Italian Health Districts. The diagnosis of RA was certified by a qualified specialist and confirmed by ≥3 prescriptions of "specific drugs" (corticosteroids, DMARDs or "biological" agents) during 2011. Patients on "specific drugs" qualified as "active RA"; those who never had more than 4 prescriptions in the past w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 26 publications
5
53
1
2
Order By: Relevance
“…Rheumatoid arthritis (RA), a chronic systemic disease, is featured with inflammatory synovitis, which can lead to destruction on bone and cartilage and even cause disability [1,2]. The incidence of RA is higher in women and older people than that in man and younger people [3]. The pathogenesis of RA is induced by complicated factors, including alteration of gene expression, environmental change and other reasons [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA), a chronic systemic disease, is featured with inflammatory synovitis, which can lead to destruction on bone and cartilage and even cause disability [1,2]. The incidence of RA is higher in women and older people than that in man and younger people [3]. The pathogenesis of RA is induced by complicated factors, including alteration of gene expression, environmental change and other reasons [4].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Globally the prevalence of rheumatoid arthritis ranging from 0.1 -1.0% and varies according to geographical location even within the same country. [6][7][8][9] The prevalence of rheumatoid arthritis reported in studies from south of Pakistan was 0.14%, whereas it was reported 0.55% in the northern part of the country. 10,11 According to European League Against Rheumatism (EULAR) recommendations, the treatment of rheumatoid arthritis must be based on a shared decision between rheumatologist.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The pathogenesis of RA is still not very clear. Substantial data have demonstrated that RA is the result of interaction among genetics, abnormal immune responses, and environmental triggers.…”
Section: Introductionmentioning
confidence: 99%